1968
DOI: 10.1021/cr60254a002
|View full text |Cite
|
Sign up to set email alerts
|

The reverse Diels-Alder or retrodiene reaction

Abstract: The reverse Diels-Alder reaction, or as the German literature refers to it, the retrodiene decomposition, is almost as old as the Diels-Alder itself. In 1929 Diels and Alder1 reported the preparation of the adduct of to react with acetylenedicarboxylic ester for 2 hr at 200°, gives 4-methylphthalic acid and 3-methyl-l-CH,•CTKCHj).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
125
0
1

Year Published

1971
1971
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(130 citation statements)
references
References 15 publications
(17 reference statements)
4
125
0
1
Order By: Relevance
“…The Diels-Alder cycloaddition reac-tion [24][25][26] and thiol-ene chemistry [27,28] have recently been introduced as alternative click routes for providing new materials. Click reactions have been widely used for the synthesis of polymers with different compositions and topologies, ranging from linear (telechelic [29], macromonomer [30,31], macrophotoinitiator [32,33] and block co-polymer [34][35][36]) to nonlinear macromolecular structures (graft [37][38][39], star [40,41], miktoarm star [42,43], H-type [44], dendrimer [45][46][47], dendronized linear polymers [48,49], macrocyclic polymers [50,51], self-curable polymers [52][53][54], network systems [55,56] and polymeric nanoparticles [14,57]).…”
Section: Introductionmentioning
confidence: 99%
“…The Diels-Alder cycloaddition reac-tion [24][25][26] and thiol-ene chemistry [27,28] have recently been introduced as alternative click routes for providing new materials. Click reactions have been widely used for the synthesis of polymers with different compositions and topologies, ranging from linear (telechelic [29], macromonomer [30,31], macrophotoinitiator [32,33] and block co-polymer [34][35][36]) to nonlinear macromolecular structures (graft [37][38][39], star [40,41], miktoarm star [42,43], H-type [44], dendrimer [45][46][47], dendronized linear polymers [48,49], macrocyclic polymers [50,51], self-curable polymers [52][53][54], network systems [55,56] and polymeric nanoparticles [14,57]).…”
Section: Introductionmentioning
confidence: 99%
“…96 The angular fused triquinane structure eventually devised for 5 D Structurally speaking the tricyclic core of the product was clearly derived from the angular meta adduct and had remained intact at expense of the cyclopropane while the methoxy group had seemingly undergone a 1,2 migration from carbon a to b (as labelled in Scheme 4.1.6). It should be noted that the 1 H NMR of this new oxasilphinene 5 D also corresponded to that seen in the reaction of protonated meta adducts 2 and 3, that we had been unable to isolate pure.…”
Section: 3mentioning
confidence: 99%
“…8 The Diels-Alder reaction can be reversible; this reaction is called the retro Diels-Alder reaction and is used to synthesize strained, interesting olefins. [9][10][11][12][13] Heterocyclic and polycyclic molecules obtained via Diels-Alder or retro Diels-Alder reactions are very important in organic chemistry and they are used as starting materials in the pharmacology and other fields. In our recent studies, we reported the reaction between 2,3-dimethyl-1,3-butadiene and dimethyl 7-oxabicyclo[2.2.1]hepta-2,5-diene-2,3-dicarboxylate with catalysts, i.e.…”
Section: Introductionmentioning
confidence: 99%